Randomized trial to evaluate contraceptive efficacy, safety and acceptability of a two-rod contraceptive implant over 4 years in the Dominican Republic - M.J. Steiner; V. Brache; D. Taylor; R. Callahan; V. Halpern; A. Jorge; S. Wevill; J. Sergison; L. Venkatasubramanian; L. Dorflinger (Elsevier, 2019)
Objective: Sino-implant (II) is a contraceptive implant that had a commodity price one-third of the competing products a decade ago. To make Sino-implant (II) more widely available, we conducted a trial to collect safety and efficacy data required for World Health Organization (WHO) prequalification, a quality standard allowing global donors to procure a pharmaceutical product. Study design: This was a randomized controlled trial allocating 650 participants to either Sino-implant (II) or Jadelle®. Participants were seen at 1 and 6 months, and then semiannually. The primary efficacy measure was the pregnancy Pearl Index [number of pregnancies per 100 women-years (WY) of follow-up] in the Sino-implant (II) group during up to 4 years of implant use. Results: For the primary outcome, Sino-implant (II) had a 4-year Pearl Index of 0.74 (95% confidence interval, 0.36-1.37) compared to 0.00 (95% confidence interval, 0.00-1.04) for Jadelle®. The Sino-implant (II) pregnancy rate was significantly higher in the fourth year (3.54 per 100 WY) than in the first 3 years combined (0.18 per 100 WY; p<.001). Total levonorgestrel concentrations were equivalent between groups at month 12, but were 19%, 22% and 32% lower in the Sino-implant (II) group at months 24, 36 and 48, respectively (p<.001 at each time point). Safety and acceptability of the two products were similar, while providers documented significantly higher breakage rates during removal of Sino-implant (II) (16.3% vs. 3.1%; p<.001). Conclusion: Based on these results, WHO prequalified Sino-Implant (II) with a 3-year use label in June 2017, 2 years shorter than the 5-year duration of Jadelle®. Implications: WHO prequalification allows global donors to procure Sino-implant (II), which means women in many low resource countries will have greater access to highly effective and acceptable contraceptive implants. Our study noted important clinical differences, including shorter duration of high effectiveness with Sino-implant (II) when compared to the other available two-rod system, Jadelle®. Introduction strategies should include appropriate training on these differences. Keywords: Sino-implant, Levoplant, Long-acting reversible contraceptive, Contraceptive effectiveness, safety